Prolonged support with Impella 5.0: different pathways of care for acute cardiogenic shock. (2nd May 2022) - Pieri, M; Ortalda, A; Ajello, S; Altizio, S; Nardelli, P; Scandroglio, AM
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Severe acute cardiogenic shock is a life-threatening condition associated with high in-hospital mortality. Impella 5.0 is a transcatheter left ventricular assist device that ensuring up to 5 L/min of blood flow can provide full hemodynamic support as bridge to recovery, heart transplantation or long term mechanical circulatory support (MCS). Purpose: To assess role and outcomes of Impella 5.0 device as tMCS in deep acute cardiogenic shock and describe the results of different pathways of care in these patients. Methods: All consecutive patients who underwent Impella 5.0 implantation for cardiogenic shock at our institution between January 2018 and June 2021 were included in the study. Results: A total of 40 patients, primarily males (85%) with a median age of 62 (54-70) years, underwent axillary Impella 5.0 implantation for severe cardiogenic shock (SCAI CS stage D: n= 12, 30%; stage E: n= 28, 70%), due to de novo onset acute myocardial infarction in 70% of patients. One third of the patients had been resuscitated and 90% were already on short term mechanical circulatory support (35% on V-A ECMO): median ejection fraction at implantation was 10 (5-20)%. Twenty-eight patients survived to next therapy or recovery (70%). Eleven patients (28%) experienced recovery and were weaned from MCS, 10 underwent LVAD implantation (25%), and seven (17%) were bridged to cardiac transplantation. Median duration of Impella support was 13 days (maximum duration 52 days), and, thanks to axillary approach, 33% were successfully mobilized during support. Device complications were limited, the most frequent being major haemolysis (28%), bleeding from cannulation site (13%), and device malfunction requiring replacement (20%), and with other complications incidence < 5%. Hospital survival was 60% overall: 100% in recovery patients, 90% in patients bridged to LVAD and 57% in patients underwent heart transplantation. Main cause of death was multiorgan failure (n=6). "Recovery" patients compared to "non-recovery" (figure 1 and2) had lower SCAI CS stage (p= 0.037), lower diabetes incidence (9% vs 48%, p=0.02) were less likely to be already on MCS support (73% vs 96%, p= 0.025) and had undergone a faster upgrade of support to Impella 5.0 (2 vs 4.5 days, p= 0.04). Conclusions: Temporary support with Impella 5.0 proved to have a key role in the management of cardiogenic shock, and showed high survival with low complication rate in these critical patients. Restoring hemodynamic and end-organ perfusion allows to get over the phase of shock and prolonged support allows pathways towards cardiac recovery or next therapies. The early identification of prognostic factors for hemodynamic recovery is crucial, since it may simplify selection for LVAD vs transplantation listing and in the timing of bridging to next therapy.